Keeping It Private: The Impossibility of Abandoning Ownership and the Horror Vacui of the Common Law of Property - von Schütz, Konstanze (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2021)
In the common law of property, it is generally impossible to abandon one’s ownership. In this article, I explore this impossibility. I show that owners cannot abandon land and chattels, let alone have a legal right to do so. I then put forth an account of the common law’s restrictive attitude toward abandonment. I demonstrate how this attitude can only be fully understood in light of the common law’s conception of ownership. This is because the fear that motivates the restrictions on abandonment, the common law of property’s horror vacui, is a fear of the absence of common law ownership in its specific normative significance. Crucial features that characterize common law ownership and that shape the legal rules on abandonment are: 1) its monism, 2) its grounding in a private ownership paradigm, and 3) its assignment of proprietary responsibility exclusively to private owners. Owing to these features, recourse to a model of “public ownership of last resort” to appease the horror—as in France and Quebec’s civil law—is barred. The only way for the common law to appease the horror is to ensure that ownable things are kept in private hands for as long as possible. The common law must “keep it private.” An account that identifies the legal rules on abandonment as catering to the common law’s urge to “keep it private” comprehensively captures the entirety of the legal rules concerning the abandonment of ownership. It shows why obliging owners to continue to assume the responsibility associated with being an owner is warranted.